Hessdalen Lights and Piezoelectricity from Rock Strain - Paiva, Gerson; Taft, C. A. (Journal of Scientific Exploration, 2011)
Hessdalen lights (HL) are unexplained light balls usually seen in the valley of Hessdalen, Norway. Some theories, such as that of Takaki and Ikeya, explain HL as a product of piezoelectricity generated under a rock strain because many crystal rocks include quartz grains which produce an intense charge density. In this work, based on the dusty plasma theory of HL (Paiva and Taft), we suggest that piezoelectricity of quartz cannot explain a peculiar property assumed by the HL phenomenon—the presence of geometrical structures in its center. Keywords: Hessdalen lights—piezoelectricity—dusty plasma